If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 7 + 3x = 115 Reorder the terms: 7 + 6x + 3x = 115 Combine like terms: 6x + 3x = 9x 7 + 9x = 115 Solving 7 + 9x = 115 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 9x = 115 + -7 Combine like terms: 7 + -7 = 0 0 + 9x = 115 + -7 9x = 115 + -7 Combine like terms: 115 + -7 = 108 9x = 108 Divide each side by '9'. x = 12 Simplifying x = 12
| -8(4b-7)=-24+8b | | 5/8÷21/4 | | 2x-4=9r-88 | | 11x^2-3780x-360=0 | | 4x+26=13+4x | | 8(X-5)=6x-16 | | 4=36/t | | 216/250 | | Y=6x-2-x | | 2a^2+12=4a^2-20 | | 4n+n=-6+4n | | 7x+25=4 | | 6x-3=17-4x | | 5/6(x)-1/3=2x-5 | | 4(6p-7)=-4p | | .375(c+8)=-1.5 | | 25=3s-4b | | 5/6(x)-1/3 | | 17=-8-9y | | 32.4=.6y+.52x | | 40=.20x+20 | | 3/4w=21 | | 16x+27=91 | | -18K=37 | | 4(6p-7)=-2(1-8b) | | 4x+25=7 | | 32.4=.6x+.52y | | 3ab+4b=12 | | 29=-6b-13 | | n/5-7=18.6 | | 3x(-x+6x-15x)= | | 3x+21=7(x-1) |